Two new species of Mesonemoura (Plecoptera: Nemouridae) from Yunnan Province of China - Xiao, Qian; Zhao, Jing; Qian, Yu-Han; Du, Yu-Zhou (Zootaxa, 2019)
Two new species of the nemourid genus Mesonemoura from Yunnan Province of southwestern China are described, M. longiflagellata Xiao & Qian sp. nov. from Pudatcuo National Park of Shangri-la City and M. tumida Qian & Du sp. nov. from Cangshan Mountian of Dali City. The male and female terminalia of the new species are compared to related species.